Potret Kajian Islam Ma’had Madinatuddiniyah Sirajul Muna - Albi, Ahmad Tahfizul; Tanjung, Muaz (Kamaya: Jurnal Ilmu Agama, 2023)
This study discusses the description of the routine study of Ma'had Madinatuddiniyah Sirajul Muna. The method that the author uses in this research is a qualitative descriptive method, that is, raising a problem that explores the social situation that will be studied widely and in depth which is carried out in Ma'had Madinatuddiniyah Sirajul Muna located in Bandar Setia Village, Percut Sei Tuan District, Deli Serdang Regency from March to May 2023 with interview and observation techniques. The results obtained in this study can be concluded that the purpose of forming a routine study of Ma'had Madinatuddiniyah Sirajul Muna is to increase the understanding of Islamic Religious Education material for the community in Percut Sei Tuan Village and its surroundings. This activity is carried out for adults on Monday and Wednesday, while for those who are landfill every day at the Sirajul Muna recitation hall which coincides in Bandar Setia Village. This routine study activity is filled with material on Tawhid, Sufism and Fiqh, the learning methods used are lectures, advice and also questions and answers.